Mini Seri Scrapbook's Review untuk meningkatkan Pembelajaran Sejarah Siswa Sekolah Menengah Pertama - Erma Mardiyyah (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve learning on history through mini serial scrapbook’s review for the seventh grade students in the Junior Secondary School 1 Baleendah. The scrapbook was implemented as project-based learning model with key pictures organized in meaningful album. Project-based learning was meant for improving the students’ knowledge, skills, and attitude. Project was meant to improve the students’ knowledge and skills. While scrapbook review was meant to improve their attitude. An experimental design was implemented with One Group Pretest and Posttest. Data were analyzed using descriptive and inferential statistics. Descriptively, the students’ knowledge and skill’s mean scores were improved from 61 to 85 and 45 to 88 respectively. The students’ attitude was also improved from the mean score of 70% to 90% respectively. The 93.8% students responded positively to mini serial scrapbook review and 100% intended to continue using this learning model.